La notion de persona et la question des affects en histoire des sciences et des savoirs. Le cas des savoirs européens sur l’anthropophagie (1770-1800) - Nicolas Cambon (Les Cahiers de Framespa)
This article presents the concept of persona, used to study the actors of a knowledge in an approach situated between the biography and the social institution. The latter are thus placed in a larger frame of references, shared by their peers, forming a collective with a recognizable public image. In so doing, the aim of this article is to show that the persona constitutes an effective tool to question the affective environment of the actors of knowledge in the past, an approach that has not yet been explored in this historiographic field. This study will be based on a specific research field: the construction of European knowledge on anthropophagy in the last quarter of the 18th century. Three personae actively contribute to this research: the naval officer, the philosopher, and the embarked scholar. The aim is to show that these three figures have a specific affective universe, influencing their perceptions and representations.